Telemedicine Curriculum in an Ophthalmology Residency Program - Aziz, Kanza; Sherif, Noha A.; Meshkin, Ryan S.; Lorch, Alice C.; Armstrong, Grayson W. (Journal of Academic Ophthalmology, 2022)
Background The COVID-19 pandemic has accelerated the adoption of telemedicine in the field of ophthalmology. Despite the increasing utilization of telemedicine, there is a lack of formal training in ophthalmology residency programs to ensure ophthalmologists are prepared to conduct virtual eye exams.Objective This article aims to assess the impact of an ophthalmic telemedicine curriculum on ophthalmology residents' self-reported knowledge acquisition in conducting telemedicine eye exams, perceived ability to diagnose, manage, and triage common eye diseases, and evaluate their attitudes toward the current and future use of teleophthalmology.Methods This single-center study at Massachusetts Eye and Ear used a nonvalidated pre- and postcurriculum survey conducted during the 2020 to 2021 academic year among ophthalmology residents. Participants engaged in an ophthalmic telemedicine curriculum that consisted of interactive didactic lectures and electronic postdidactic assessments.Results Twenty-four residents (100%) completed a precurriculum survey, while 23 of 24 (95.8%) residents completed both the telemedicine curriculum and a postcurriculum survey. On a five-point Likert scale, the median interquartile range (IQR) scores for confidence with setup/logistics, history taking, examination, documentation, and education increased from 2.5 (2.0–4.0) to 4.0 (3.5–4.5) (p = 0.001), 3.0 (3.0–4.0) to 5.0 (4.0–5.0) (p < 0.001), 2.0 (1.8–2.0) to 4.0 (3.5–4.0) (p < 0.001), 2.0 (1.0–2.0) to 4.0 (3.0–4.0) (p < 0.001), and 2.5 (2.0–3.0) to 4.0 (4.0–4.0) (p < 0.001), respectively. The median (IQR) scores for comfort with ethics/professionalism, disparities and conducting patient triage, diagnosis, and management increased from 2.0 (2.0–2.3) to 4.0 (3.0–4.0) (p < 0.001), 2.0 (2.0–2.0) to 3.0 (3.0–4.0) (p < 0.001) and 3.0 (2.0–3.0) to 4.0 (3.0–4.0) (p = 0.001), 2.0 (2.0–3.0) to 3.0 (3.0–4.0) (p < 0.001), and 3.0 (2.0–3.0) to 3.0 (3.0–4.0) (p = 0.008), respectively.Conclusion The implementation of an ophthalmic telemedicine curriculum increased resident confidence and self-reported knowledge across all logistical and clinical components of virtual ophthalmic care. Formal telehealth curricula can address an unmet educational need of resident trainees in an era of rapid uptake and utilization of telehealth services.
Keywords: resident education; ophthalmology; telemedicine; curriculum development; graduate medical education